Risk factors for tuberculosis: diabetes, smoking, alcohol use, and the use of other drugs - Silva, Denise Rossato (J Bras Pneumol, 2018)
Tuberculosis continues to be a major public health problem. Although efforts to control the epidemic have reduced mortality and incidence, there are several predisposing factors that should be modified in order to reduce the burden of the disease. This review article will address some of the risk factors associated with tuberculosis infection and active tuberculosis, including diabetes, smoking, alcohol use, and the use of other drugs, all of which can also contribute to poor tuberculosis treatment results. Tuberculosis can also lead to complications in the course and management of other diseases, such as diabetes. It is therefore important to identify these comorbidities in tuberculosis patients in order to ensure adequate management of both conditions.